First report of Fusarium oxysporum f. sp. cubense Tropical Race 4, causing Fusarium wilt in Cavendish bananas in Peru - Acuña, Rosalyn; Rouard, Mathieu; Leiva Sandoval, Ana Maria; Marques, Claudio; Olortegui, Arturo; Ureta, Cledy; Cabrera-Pintado, Rosa M.; Rojas, Juan Carlos; López, Diana; Cenci, Alberto; Cuéllar, Wilmer Jose; Dita Rodriguez, Miguel Angel (Scientific Societies, 2022)
Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4), the causal agent of Fusarium wilt of banana (FWB), is currently the major threat to the banana industry worldwide (Dita et al. 2018). Restricted to South Asia for more than 20 years, Foc TR4 has spread in the last years to the Middle East, Mozambique, and Colombia (García-Bastidas et al. 2019; https://pestdisplace.org/embed/news/map/disease/11). The incursion of Foc TR4 in Colombia increased awareness and prevention efforts across Latin American and the Caribbean (LAC). However, new Foc TR4 outbreaks in LAC countries were considered a matter of time. In April 2021, banana (Musa spp., Cavendish, AAA) plants (30% of incidence) showing typical symptoms of FWB, such as leave yellowing, wilting and vascular discoloration were observed in one farm (about 1 ha) located in Querecotillo, Peru (4°43’54.84”S 80°33’45.00”W). Mycological analyses of samples (pseudostem strands) collected from 10 symptomatic plants were performed as described by Dita et al. (2010). These analyses revealed a continuous presence of fungal colonies identified as Fusarium oxysporum species complex. Molecular diagnostics targeting two different genome regions (Dita et al 2010; Li et al. 2013) identified nine of these isolates as Foc TR4. These results were further confirmed by qPCR analyses using the commercial Clear Detections TR4 kit. The genome of four single-spore isolates (PerS1, PerS2, PerS3 and PerS4) was sequenced using the Illumina platform (MiSeq Kit, 2x151 bp Paired-End). The strain PerS4 was also sequenced using Oxford Nanopore (FLOW-MIN111; R10.3 chemistry) as described by Lopez-Alvarez et al., (2020).